Cancer Theranostics with Near-Infrared Light-Activatable Multimodal Nanoparticles - Melancon, Marites P. (2011)
[Image: see text] Nanomaterials that interact with light provide a unique opportunity for biophotonic nanomedicine. Multifunctional nanoparticles (NPs) that have strong and tunable surface plasmon resonance absorption in the near-infrared region combined with visibility with multiple imaging modalities (magnetic resonance imaging, nuclear imaging, and photoacoustic imaging) have great potential in image-guided therapies. These novel nanostructures, once introduced, are expected to home to solid tumors via the enhanced permeability and retention effect (a passive targeting mechanism) or via targeting ligands bound to their surfaces (an active targeting mechanism). The primary mode of action for photothermal conducting NPs is to convert photoenergy into heat, causing temperature in the treatment volume to be elevated above the thermal damage threshold, which results in irreversible cell killing. It is now recognized that this process, termed photothermal ablation therapy or PTA, although very effective, is unlikely to kill all tumor cells when used alone. In addition to PTA, photothermal conducting NPs can also efficiently trigger drug release and activate RNA interference. Such a multimodal approach, which permits simultaneous PTA therapy, chemotherapy, and therapeutic RNA interference, should provide an opportunity for complete eradication of residual disease. In this Account, we provide an up-to-date review of the synthesis and characterization, functionalization, and in vitro and in vivo evaluation of NIR light-activatable multifunctional nanostructures used for imaging and therapy, with an emphasis on hollow gold nanospheres, magnetic core–shell gold nanoshells, and semiconductor copper monosulfide NPs. We discuss three types novel drug delivery systems in which hollow gold nanospheres are used to mediate controlled drug release.